Vitamin D status and fertility outcomes during winter among couples undergoing in vitro fertilization/intracytoplasmic sperm injection. Issue 2 (November 2016) - Neville, Grace; Martyn, Fiona; Kilbane, Mark; O'Riordan, Mairead; Wingfield, Mary; McKenna, Malachi; McAuliffe, Fionnuala M.
Abstract: Objective: To assess the vitamin D status of men and women undergoing in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI), and to investigate associations between vitamin D status and fertility variables. Methods: A cross-sectional prospective study was undertaken of men and women attending a fertility clinic in Ireland for IVF/ICSI between January and March 2014. Vitamin D status was determined by measurement of serum 25-hydroxyvitamin D (25(OH)D). Questionnaires examined knowledge and practices concerning vitamin D. Fertility variables and pregnancy outcomes were assessed in relation to vitamin D status. Results: Overall, 73 men and 64 women provided blood samples. Among men, no correlation was found between 25(OH)D and total motility (ρ = 0.069, P = 0.562), progressive motility (ρ = 0.066, P = 0.576), count (ρ = 0.001, P = 0.996), or morphology (ρ = –0.034, P = 0.774) of sperm. Additionally, there was no association between 25(OH)D and ongoing pregnancy rates ( P = 0.158). There was no difference in 25(OH)D between men with and without male factor subfertility issues ( P = 0.856). Among women, there was no significant correlation between 25(OH)D and anti-Müllerian hormone ( P = 0.629) or number of collected ( P = 0.198) and fertilized oocytes ( P = 0.136). There was no difference in 25(OH)D between women with and without ongoing pregnancy ( P = 0.222). Conclusion: No correlation was found between fertility variables or pregnancy outcomes and male or female vitamin D status.